ANALISA FAKTOR YANG MEMPENGARUHI KEKAMBUHAN PASIEN GANGGUAN JIWA DENGAN MODEL STRES ADAPTASI STUART DI RUMAH SAKIT JIWA DAN KETERGANTUNGAN OBAT SEMBADA MEDAN - Maximilianus Dasril Samura; Tellen Marlina Tellen (JURNAL KESMAS DAN GIZI (JKG), 2019)
Mental disorders are very dangerous even it does directly cause death, but will cause deep suffering for the individual and a heavy burden on the family. The factors that cause mental disorders vary depending on the type of mental disorder experienced. This Research aims to determine the factors that affect relapse of mental disorder patients in the Sembada Medan Mental Hospital and Drug Dependency 2019. This research is quantitative with a cross sectional approach and sampling with a purposive sample technique. This research was conducted on 28 respondents with research variables are factors of compliance, family support, and social support. From the research that has been done, it was found that the majority of respondents aged between 31 - 46 years (64.3%), based on the sex of the respondents, the majority were male (60.7%), based on the environmental characteristics of the majority urban respondents (64.3%) , based on the family support of the respondents, the majority were good (57.1%), based on the respondents' compliance, the majority was not good (60.7%), based on environmental support the majority were not good (67.9%) ) The results of the Chi-square test show a significance value of p (0.008) Î± <(0.05) which means that there are significant factors between adherence, family support, and social support for recurrence in the Mental disorders Hospital and Drug Dependency Medan in 2019. It is recommended for psychiatric patients to be more obedient in taking drugs as recommended by doctors in the Mental sicknes Hospital and Drug Dependency Medan in 2019.